Two new species of Allophrys Förster from the Oriental Region (Hymenoptera: Ichneumonidae: Tersilochinae) - Yue, Qi; Reshchikov, Alexey; Ang, Yuchen; Xu, Zai-Fu; Pang, Hong (Zootaxa, 2017)
Two species of Allophrys Förster are described from the Oriental region, A. cantonensis Reshchikov& Yue, sp. nov., collected from Guangdong, China and A. falcatus Reshchikov, sp. nov. from Davao, Philippines. This is first record of the genus from China. A key to the Oriental species of the genus is provided.